THE EFFECT OF THE COMBINATION OF BENSON THERAPY AND QUR'ANIC MUROTTAL ON ANXIETY IN POST-APPENDECTOMY PATIENTS - Ucu Yuliati; Betie Febriana; Wahyu Endang (The Shine Cahaya Dunia D-III Keperawatan, 2026)
Background: The prevalence of appendicitis worldwide continues to rise, reaching 259 million cases in 2022, with a mortality rate of up to 21,000. The most common medical treatment for acute appendicitis is surgery (appendectomy). Post-surgery often causes anxiety in patients related to the recovery of bodily functions, fear, pain, complications, and feelings of helplessness, which impact quality of life and recovery time. This study aims to determine the impact/influence of a combination of Benson therapy and Quranic recitation therapy on the anxiety levels of post-appendectomy patients at Sari Asih Hospital, Karawaci. Results: This study provided a combination of therapies and analyzed the results in post-appendectomy patients in the treatment group using the Marginal Homogeneity test, which found a difference in anxiety levels with a p-value of 0.000 after the combination therapy intervention. Meanwhile, the Kolmogorov-Smirnov test resulted in a p-value of 0.028, indicating a difference in anxiety levels between the control and treatment groups after the combination therapy intervention. Conclusion: This study shows evidence of the effect of the combination of Benson therapy and Quranic recitation on reducing anxiety in post-appendectomy patients at Sari Asih Hospital, Karawaci.